The Foot Arch and the Physical Efficiency of Children in the Younger School Age - Ignasiak, Zofia; Kurowska, Janina (Anthropological Review, 1988)
The Foot Arch and the Physical Efficiency of Children in the Younger School Age were investigated. On the basis of continuous studies, the authors observed, the increase of the Clarke’s angle in urban children in the age of 7-9 years. Relations were found between the longitudinal arcli of the foot and selected motoric properties. The description includes also the basic morphological.characteristics, i. e. the stature and body weight.